(untitled) (Bangladesh Journal of Medical Science, 2023)
Background: The intensity of the COVID-19 epidemic process in the administrative territories of Ukraine differs. Risk factors for the spread of this infection have not been sufficiently studied, which prevents the development of adequate preventive and anti-epidemic measures at the local level. Objectives: Conduct an epidemiological analysis of the incidence of COVID-19 in the regions of the Northern part of Ukraine and identify the leading risk factors for spread. Material and Methods: The incidence of COVID-19 was analyzed for 73 weeks and 28 predictors. Fourier’s spectral analysis, Feature Selection and Variable Filtering method of the Data mining module, Irwin’s method, integral visual coefficient was used. Results. There were two rises in the incidence of COVID-19, the cyclicity was 18 - 24 weeks. The conditions for the spread of COVID-19 cases in the regions of the Northern part have been established, namely: the number of people and the elderly in the family, demographic and migration processes. Violation of regime-restrictive measures leads to abnormal rises in morbidity. Conclusions. The epidemic situation in the Northern part remains volatile, as there are conditions for the spread of COVID-19 that cannot be eliminated, as well as some, that need to be developed (tourism, demographic processes, financing, etc.). Therefore, compliance with restrictive measures and vaccination of the population of the region remain the main preventive measures. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 778-784